The Impact of AI-Based Marketing, Chatbots, and Social Media on Customer Satisfaction and the Economic Behavior of MSMEs Consumers in Jambi City - Prasasti, Laura; Fahdillah, Yosi; Pangestu, Mira Gustiana (Universitas Muhammadiyah Sorong, 2026)
This study investigates the influence of AI-based marketing, chatbot services, and social media activities on customer satisfaction and consumer economic behavior among Micro, Small, and Medium Enterprises (MSMEs) in Jambi City. A quantitative approach was applied, and data were collected from 400 respondents using a structured questionnaire. The analysis was conducted using Structural Equation Modeling (SEM) with SmartPLS 4. The results indicate that AI-based marketing, chatbot services, and social media engagement each have a significant positive effect on customer satisfaction. Furthermore, customer satisfaction significantly influences consumer economic behavior. The study also finds that customer satisfaction mediates the relationship between digital marketing strategies and consumer behavior. These findings highlight the strategic role of digital technologies in enhancing customer experiences and shaping consumer engagement in the MSME sector.